Temperature stability of oxytocin ampoules labelled for storage at 2°C–8°C and below 25°C: an observational assessment under controlled accelerated and temperature cycling conditions. Issue 7 (26th July 2019) - Nguyen, Tri-Hung; Lambert, Peter; Minhas, Rajpreet Singh; McEvoy, Claire; Deadman, Kim; Wright, Philip; Prankerd, Richard J; Mogatle, Seloi; McIntosh, Michelle P
Abstract : Introduction: Oxytocin, administered via injection, is recommended by WHO for the prevention and treatment of postpartum haemorrhage. However, the susceptibility of oxytocin injection to thermal degradation has led WHO and UNICEF to recommend cold-chain storage of all oxytocin products. Nevertheless, some oxytocin products supplied to the global market are labelled for storage at ≤25°C, often with a shorter shelf-life relative to products labelled for refrigeration. Differences in labelled storage requirements can lead to uncertainties among stakeholders around the relative stability of oxytocin products and specifically whether ≤25°C products are more resistant to degradation. Such confusion can potentially influence policies associated with procurement, distribution, storage and the use of oxytocin in resource-poor settings. Objectives: To compare the stability of oxytocin injection ampoules formulated for storage at ≤25°C with those labelled for refrigerated storage. Design: Accelerated and temperature cycling stability studies were performed with oxytocin ampoules procured by the United Nations Population Fund (UNFPA) from four manufacturers. Method: Using oxytocin ampoules procured by UNFPA, accelerated stability (up to 120 days) and temperature cycling (up to 135 days between elevated and refrigerated temperatures) studies were performed at 30°C, 40°C and 50°C. Oxytocin content was quantified using a validated HPLC-UV method. Results: All ampoules evaluated exhibited similar stability profiles under accelerated degradation conditions with the exception of one product formulated for ≤25°C storage, where the rate of degradation increased at 50°C relative to other formulations. Similar degradation trends at elevated temperatures were observed during temperature cycling, while no significant degradation was observed during refrigerated periods of the study. Conclusion: Oxytocin ampoules formulated for non-refrigerated storage demonstrated comparable stability to those labelled for refrigerated storage and should not be interpreted by stakeholders as offering a more stable alternative. Furthermore, these products should not be procured for use in territories with high ambient temperatures, where all oxytocin injection products should be supplied and stored under refrigerated conditions.